You Win Some, You Lose Some: Toward a Comprehensive Understanding of the Trade-Off Impacts of Leader High Performance Expectations - Wang, Zhen (Journal of business ethics, 2026)
While leaders’ high performance expectations (LHPEs) are often considered and proposed as an effective performance management tool, this viewpoint may be insufficient because it solely considers the performance gains without addressing potential ethical costs. This study deviates from previous beliefs by demonstrating how leaders’ high performance expectations are divergently related to employee performance as well as prescriptive immorality (e.g., performance-improving noncompliant behavior, PINB) and prescriptive morality (e.g., organizational citizenship behavior, OCB). Drawing on goal-shielding theory, we propose an integrated model in which LHPE improves employee work performance by prompting them to prioritize performance goals. This same mechanism, however, elevates PINB and reduces OCB, with these effects being more pronounced in highly competitive team climates. The multilevel path analyses of a three-wave, time-lagged survey dataset containing 232 employees and their leaders from 59 teams supported our hypotheses. These findings highlight both the performance benefits and ethical costs associated with LHPE, underscoring the importance of managers balancing performance demands with ethical considerations when employing LHPE as a performance management strategy.